Assessment of wind power plant performance using turbine performance and power curves: a case study of PLTB TOLO I Jeneponto - Idris, Ahmad Rosyid; Latif, Muh. Ardiansyah; Thaha, Sarma; Asri, Andarini; Thahir, Muhammad; Sidehabi, Sitti Wetenriajeng; Sofyan, Sofyan (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
Jeneponto Regency in South Sulawesi possesses significant wind potential, making it an ideal location for the development of Wind Power Plants (WPP). However, these WPPs are intermittent due to the inconsistent nature of wind energy, presenting challenges that affect the performance and efficiency of turbines in generating electricity. Therefore, this study aims to evaluate the performance of the SWT-3.6-130 wind turbines at the Tolo 1 WPP in Jeneponto to determine their capability in converting wind energy into electrical energy at specific wind speeds. The evaluation results indicate that the performance of the SWT-3.6-130 wind turbines at the Tolo WPP in February 2022 was not optimal. The maximum output power generated by these turbines approached the maximum capacity of 3.6 MW, with Turbine 06 producing 3.57 MW at a wind speed of 13.07 m/s, Turbine 09 producing 3.57 MW at a wind speed of 12.27 m/s, and Turbine 013 producing 3.58 MW at a wind speed of 12.11 m/s. Although the power generated was close to the maximum capacity, the performance variation among turbines indicates the need for further evaluation to address factors reducing efficiency. Power coefficient analysis shows that Turbine T13 exhibited the best performance, with the fewest instances of power coefficient values not meeting standards. This study provides crucial insights for improving performance and preventing failures at the Tolo WPP in the future.